2006
DOI: 10.1074/jbc.m607545200
|View full text |Cite
|
Sign up to set email alerts
|

Combined Leptin Actions on Adipose Tissue and Hypothalamus Are Required to Deplete Adipocyte Fat in Lean Rats

Abstract: Intense hyperleptinemia completely depletes adipocyte fat of normal rats within 14 days. To determine the mechanism, epididymal fat pads from normal wild-type (؉/؉) and obese (fa/fa) Zucker Diabetic Fatty (ZDF) donor rats were transplanted into normal ؉/؉ and fa/fa ZDF recipients. Hyperleptinemia induced by adenovirus-leptin administration depleted all fat from native fat pads and from fat transplants from ؉/؉ donors but not from transplants from ZDF fa/fa donors with defective leptin receptors. In both native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Under the present experimental conditions, amylin pretreatment was not associated with altered Lep, Lepr, or Socs-3 gene expression or pSTAT3 levels in WAT; however, leptin-mediated fat depletion has been shown to follow a complex time course arising from a combination of paracrine, hypothalamic, and sympathetic (catecholaminergic) effects (19,34). Hence, the interrogation of selected downstream genes/effectors of leptin at a single time point does not exclude the possibility that different durations of amylin or amylinϩleptin treatment could enhance direct leptin receptor or postreceptor events at the level of the adipocyte.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Under the present experimental conditions, amylin pretreatment was not associated with altered Lep, Lepr, or Socs-3 gene expression or pSTAT3 levels in WAT; however, leptin-mediated fat depletion has been shown to follow a complex time course arising from a combination of paracrine, hypothalamic, and sympathetic (catecholaminergic) effects (19,34). Hence, the interrogation of selected downstream genes/effectors of leptin at a single time point does not exclude the possibility that different durations of amylin or amylinϩleptin treatment could enhance direct leptin receptor or postreceptor events at the level of the adipocyte.…”
Section: Discussionmentioning
confidence: 49%
“…Additional, complementary mechanisms underlying the observed synergy could include amylin potentiating leptin's direct effects at the level of the adipocyte (19,33,34). Under the present experimental conditions, amylin pretreatment was not associated with altered Lep, Lepr, or Socs-3 gene expression or pSTAT3 levels in WAT; however, leptin-mediated fat depletion has been shown to follow a complex time course arising from a combination of paracrine, hypothalamic, and sympathetic (catecholaminergic) effects (19,34).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, leptin resistance can be regarded as a main factor in the initiation and development of diet-induced obesity [19]; however, it seems that this effect may not only rely on the central level, but also on the peripheral level, in which the adipose tissue can be of great importance [14]. In this sense, Wang et al have previously shown that HF-diet feeding in male rats induced a decline in OB-Rb mRNA in the adipose tissue (the authors do not specify the type of fat depot analyzed) [25].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in which recombinant adenoviruses were administered to intact rodents, the reporter gene was primarily expressed in the liver (Herz & Gerard 1993, Chen et al 1996, Park et al 2006. We used real-time PCR and western blot analysis to examine the expression of DCD in various tissues of normal 5-week-old mice that had been injected with either Ad-b-gal or Ad-DCD virus.…”
Section: Expression Of Dcd In Liver After Ad-dcd Virus Injectionmentioning
confidence: 99%